2011
DOI: 10.1088/0022-3727/44/48/482003
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and spectroscopic diagnostics of a single-stage plasma-catalysis system: effect of packing with TiO2

Abstract: The influence of adding TiO2 on the electrical and spectroscopic characteristics of a N2 dielectric barrier discharge (DBD) has been investigated in a single-stage plasma-catalysis system. The introduction of the catalyst into the electrode gap leads to a transition in the discharge behaviour. The presence of the TiO2 pellets in the discharge significantly increases the vibrational temperature of N2 in the DBD, which suggests that the interaction of plasma and catalyst has a strong effect on the electron energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
73
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 15 publications
9
73
2
Order By: Relevance
“…The space (including the space filled with pellets) averaged electric field in a plasma fully packed with packing pellets is initially increased by a factor of 1.4 when increasing the dielectric constant of the materials from 10 to 1000, above this the change in the electric field becomes negligible 36 . We have reported that the interaction of plasma and TiO 2 exhibited a strong effect on the electron energy distribution in the discharge with an increase in both highly energetic electrons and electric field 26 . This phenomenon can also be confirmed by previous work, showing that the presence of TiO 2 in a plasma leads to a significant increase of the reduced electric field 37 .…”
Section: Methodsmentioning
confidence: 98%
“…The space (including the space filled with pellets) averaged electric field in a plasma fully packed with packing pellets is initially increased by a factor of 1.4 when increasing the dielectric constant of the materials from 10 to 1000, above this the change in the electric field becomes negligible 36 . We have reported that the interaction of plasma and TiO 2 exhibited a strong effect on the electron energy distribution in the discharge with an increase in both highly energetic electrons and electric field 26 . This phenomenon can also be confirmed by previous work, showing that the presence of TiO 2 in a plasma leads to a significant increase of the reduced electric field 37 .…”
Section: Methodsmentioning
confidence: 98%
“…The combination of plasma and heterogeneous catalysis has been regarded as a promising and effective solution to overcome the drawback of plasma processes [7,11,12]. Introducing a catalyst into a plasma reactor could change the electron energy distribution function (EEDF) and generate more highly energetic and reactive species, which favour the plasma-induced reactions towards deep oxidation of VOCs [13]. The combination of plasma with catalysis has great potential to lower the activation temperature of the catalysts, enhance the removal of pollutants, and minimize the formation of unwanted by-products: all of which may contribute in different ways to the enhancement of the energy efficiency of the plasma process [7].…”
Section: Introductionmentioning
confidence: 99%
“…It reduces the amplitude of the current pulses and changes the typical filamentary mode of discharge observed in a plasma-alone DBD to a prevalent surface discharge on the packing surface and spatially limited microdischarges. [16][17][18] Suppression of the filamentary discharges in a fully packed DBD was suggested to be responsible for the negative performance. 16 An alternative packing configuration, in which the packing material (catalyst particles or dielectric pellets) are placed along the bottom of the dielectric barrier layer over the entire length of the discharge (partial packing), was evaluated.…”
mentioning
confidence: 99%